Натуралістичний імператив: "Треба пізнавати закони соціальної природи і жити в злагоді з ними!" - Костенко, О.М. (Вісник НАН України, 2025)
Науки мають забезпечувати не лише науково-технічний, а й соціальний прогрес, зокрема прогрес у сферах політики, економіки, права, моралі. Відставання так званих неприродничих, у тому числі соціальних, наук від природничих (фізика, хімія, біологія), неузгодженість між ними є небезпечними для людства. Це може призвести до того, що результати науково-технічного прогресу (ядерна зброя, штучний інтелект, біотехнології тощо) опиняться в руках людей, які перебувають у стані соціопатії чи соціального інфантилізму, що відкриває шлях до саморуйнації людської цивілізації. Тому надзвичайно актуальним вбачається пошук нових парадигм, які сприяли б розвитку наук, що забезпечують соціальний прогрес. Розглянутий у статті підхід ґрунтується на ідеї природності соціального, що проглядається в працях стоїків, Аристотеля, Цицерона, С. Оріховського, Г. Гроція, Т. Гоббса, Дж. Локка, Г. Сковороди, А. Сміта, Т. Джефферсона, Е. Дюркгейма, В.І. Вернадського та ін. “Is the social natural?” Given the signs of the crisis of modern civilization, this, from the author’s point of view, is today the main question of worldview. In searching for an answer to this question, the author relies on the idea of the naturalness of the social, which can be seen in the works of the Stoics, Aristotle, Cicero, S. Orikhovsky, H. Grotius, T. Hobbes, J. Locke, G. Skovoroda, A. Smith, T. Jefferson, E. Durkheim, V.I. Vernadsky and others. Substantiating the idea that the social is natural and exists according to the laws of social nature, which are different from the laws of physical nature and the laws of biological nature, the author proves that social sciences are sciences that learn (discover) the laws of social nature in order to harmonize social practice with them. Otherwise, social practice, inconsistent with the laws of social nature, will be a manifestation of people’s arbitrariness and illusions. This is the root cause of all kinds of anomalies in politics, economy, law, and morality. To counteract these anomalies, social practice should be guided not by the arbitrariness and illusions of people, but by the laws of social nature. This can be achieved by cultivating in society the social culture of people, which is defined as the state of coherence of their will and consciousness with the laws of social nature. This essay formulates ideas that can contribute to the development of scientific foundations for improving social practice and ensuring social progress, in particular in Ukraine.